From Tradition to Transformation: The Mediating Role of Entrepreneurial Learning and Digital Readiness in Leveraging Socio-Cultural Capital for Innovation - Hamid, Muliyadi; Safar , Ilham; Wahyu , Wahyu; Ramlawati , Ramlawati; Nurdin , Nasyirah (Vifada Management and Social Sciences, 2025)
Purpose: This study aims to examine how socio-cultural capital influences innovation among micro, small, and medium enterprises (MSMEs) in South Sulawesi through the mediating roles of entrepreneurial learning and digital readiness. The research seeks to clarify how cultural values and learning dynamics interact to shape digital and innovative capabilities within emerging market contexts. Research Design and Methodology: A quantitative approach was employed using Structural Equation Modeling Partial Least Squares (SEM–PLS) to test a double-mediation model. Data were collected from 300 MSME owners across five regencies in South Sulawesi Makassar, Gowa, Maros, Bone, and Wajo representing diverse socio-cultural and economic landscapes. The constructs were measured using validated indicators adapted from prior studies, and data were analyzed using SmartPLS 4 to assess both measurement and structural models. Findings and Discussion: The results reveal that socio-cultural capital indirectly enhances innovation through entrepreneurial learning and digital readiness. Entrepreneurial learning serves as a bridge between traditional values and digital transformation, while digital readiness translates learning outcomes into innovative practices. This indicates that innovation in culturally embedded settings arises not merely from technology adoption but from the dynamic interplay of culture, learning, and digital adaptation. Implications: The study emphasizes the need for policy and managerial interventions that integrate cultural values into innovation strategies. Strengthening culturally rooted learning ecosystems and promoting digital literacy can enhance MSME competitiveness and sustainability in emerging regions.